If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 18x = 535 Solving 13 + 18x = 535 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 18x = 535 + -13 Combine like terms: 13 + -13 = 0 0 + 18x = 535 + -13 18x = 535 + -13 Combine like terms: 535 + -13 = 522 18x = 522 Divide each side by '18'. x = 29 Simplifying x = 29
| 12+20x=132 | | (5x+1)(4x^2+2x+3)= | | 3t=-2 | | 7x^4-63x^2=0 | | 8b-6a-5a+6b= | | 3x^3=12 | | 4r=4 | | 18x^2=6x^4 | | 9p+7p+6p= | | 2x+15x= | | 59-7x=20x+17 | | x=14-8 | | 6(r-3)-2(r+5)+10= | | 56-3x=10x+17 | | p-7=9 | | 92-2x=43x+17 | | 2x^3+x^2+13x+84=0 | | 2x-4=10x-64 | | 112r^3+34r^2-6r=0 | | -4x-7y=5 | | 4(2u-3)=44 | | 2*6+{7*8}-67= | | 6a^2+13a=5 | | 18a^3b-39a^2b-15ab=0 | | -4-5x=8-8x | | 8(t-2)+6t=7(2t+2)-10 | | 6.3+.5x=16.3 | | 120-8-8-8= | | -[6x+(4x+3)]=7-(5x+6) | | 4.28-.4x=1.48 | | -2(4s-2)-4=-3(7s+5)-5 | | 2x+2=11-7x |